Papua New Guinea food price bulletin: August 2021 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Schmidt, Emily (International Food Policy Research Institute, 2021)
During April through June 2021, market price data were collected routinely by the Fresh Produce Development Agency (FPDA), providing an important baseline for future market price analysis. In addition, the team fully implemented the new tablet price data collection tools which were built to improve data collection accuracy. The new price data questionnaire has decreased the list of diverse crops for price collection to focus on greater data quality collection, while maintaining important staple crops and a selection of fruit and vegetable crops. An accompanying trader survey that asks questions about production and sales volumes, transaction costs, and market processes was piloted in early April and will be fully implemented in Quarter 3 of 2021.